Relationship marketing: development of theory and practice - L. P. Steblyakova; E. A. Vechkinzova; E. V. Krasnov (Вестник университета)
The article studies theory and practice of relationship marketing development based on the study of theoretical models’ evolution that conceptualize relationship marketing to a certain extent, taking it beyond traditional marketing complex. Further development takes place considering modern approaches to building relationships between a supplier of goods and services with consumers and partners in the context of further digitalization and “internetization” of business communications, transformation of CRM into CMR strategies of companies, network forms of business organization development, and transition from a product-centric to a client-centric structure. The prospects for relationship marketing development aimed at overcoming risks of new forms of organization, collaboration of business structures and strengthening their advantages, affirmation of consumer’s role as a direct participant in the creation of consumer value in consumer markets transformation, as well as wide spread of business ecosystems integrating the advantages of virtual business and a network form of organization have been determined, opening new opportunities for expanding collaborative innovations and obtaining a synergistic effect as a result of creating additional consumer value and building long-term multilateral relations.